Senecavirus A Entry Into Host Cells Is Dependent on the Cholesterol-Mediated Endocytic Pathway - Jia, Meiyu; Sun, Mingxia; Tang, Yan-Dong; Zhang, Yu-Yuan; Wang, Haiwei; Cai, Xuehui; Meng, Fandan (Frontiers in Veterinary Science, 2022)
Senecavirus A (SVA), an important member of the Picornaviridae family, causes vesicular disease in pigs. Here, we generated an EGFP-expressing recombinant SVA re-SVA-EGFP, which exhibited similar growth kinetics to its parental virus. The reporter SVA was used to study the role of pig ANTXR1 (pANTXR1) in SVA infection in a porcine alveolar macrophage cell line (PAM-Tang cells). Knockdown of the pANTXR1 significantly reduced SVA infection and replication in PAM-Tang cells, while re-expression of the pANTXR1 promoted the cell susceptibility to SVA infection. The results indicated that pANTXR1 is a crucial receptor mediating SVA infection. Subsequently, the viral endocytosis pathways for SVA entry into pig cells were investigated, and the results showed that cholesterol played an essential role in receptor-mediated SVA entry. Together, these results demonstrated that SVA entry into host cells through the pANTXR1-mediated cholesterol pathway. Our findings provide potential targets to develop antiviral drugs for the prevention of SVA infection in the pig population.